ANALISIS TINDAK TUTUR DALAM NOVEL DOMPET AYAH SEPATU IBU KARYA J.S KHAIREN - Gifelem, Agustinus Gideon; Howay, Regina (SOSCIED, 2025)
This study aims to find out the form of illocutional speech contained in the novel "Dompet Ayah Sepatu Ibu Karya J.S Khairen". The type of research used is qualitative descriptive. The data in this study is speech while the data source is the novel "Dompet Ayah Sepatu Ibu Karya J.S Khairen. Data collection techniques are reading techniques and recording techniques. The results of this study show that directive speech has 6 forms, namely the directive speech act of Order, Beg, Request, Suggest, Request, and Order. In J.S Khairen's novel Dompet Ayah Sepatu Ibu Karya there are 68 directive speech acts, where directive speech acts are divided into 8 directive speech acts, 1 directive speech act of begging, 13 act of directive speech requesting, 30 acts of suggestive speech, 4 acts of directive speech requests, and 12 acts of directive speech of orders